Fault Cycling and Its Impact on Hydrocarbon Accumulation: Insights from the Neogene Southwestern Qaidam Basin - Zhaozhou Chen; Zhen Liu; Jun Li; Fei Zhou; Zihao Feng; Xinruo Ma (Energies)
Building upon the geological cycle theory, this study proposes fault cycles as a critical component of tectonic cyclicity in petroliferous basins. Focusing on reservoir-controlling faults in the southwestern Qaidam Basin, we systematically analyze fault architectures and identify three distinct fault activation episodes: the Lulehe Formation (LLH Fm.), the upper part of the Xiaganchaigou Formation (UXG Fm.), and the Shizigou Formation (SZG Fm.). Three types of fault cycle models are established. These fault cycles correlate with the evolution of regional tectonic stress fields, corresponding to the Cenozoic transition from extensional to compressional stress regimes in the basin. Mechanistic analysis reveals the hierarchical control of fault cycles in hydrocarbon systems: the early cycle governs the proto-basin geometry and low-amplitude structural trap development; the middle cycle affects the source rock distribution; and the late cycle controls trap finalization and hydrocarbon migration. This study proposes a fault cycle-controlled accumulation model, providing a dynamic perspective that shifts from conventional static fault concepts to reveal fault activity periodicity and its critical multi-phase control over hydrocarbon migration and accumulation, essential for exploration in multi-episodic fault provinces.